LFA-1: A potential key player in microglia-mediated neuroprotection against oxygen-glucose deprivation in vitro - Robin Jansen; Marc Pawlitzki; Michael Gliem; Sven G. Meuth; Stefanie Schreiber; Michael-W. Görtler; Jens Neumann (PLoS ONE, 2025)
For the last 38 years, all neuroprotective agents for patients with ischemic stroke have failed in clinical trials. The innate immune system, particularly microglia, is a much-discussed target for neuroprotective agents. Promising results for neuroprotection by inhibition of integrins with drugs such as natalizumab in animal stroke models have not been translated into clinical practice. Our present study reveals the relevance of a β2 integrin, lymphocyte function-associated antigen-1 (LFA-1), as a potential key player in protecting neuronal cell death after oxygen-glucose deprivation in organotypic hippocampal cell cultures. In addition, we identified microglial cells as effector cells for LFA-1-mediated neuroprotection. The counterpart of LFA-1 on microglia is unclear, but we show strong expression of ICAM-5 in hippocampal neurons, suggesting a critical role for direct crosstalk between microglia and neurons for neuronal survival under oxygen-glucose deprivation. The enigma of neuroprotection after ischemic stroke remains to be solved, and our findings highlight the continuing importance and lack of understanding of integrin-mediated pathways after ischemic stroke and the need for further intensive research.